Monitoring of coal mining subsidence in peri-urban area of Zonguldak city (NW Turkey) with persistent scatterer interferometry using ALOS-PALSAR - Abdikan, Saygin; Arikan, Mahmut; Sanli, Fusun Balik; Cakir, Ziyadin (SPRINGER, 2014)
This paper presents the results of spatiotemporal monitoring of surface subsidence over a mining area in Zonguldak Province of Turkey using Synthetic Aperture Radar (SAR) data, providing maps of subsidence rates in the radar line of sight direction. A total of 18 SAR images, acquired between January 2007 and June 2010 by the Japanese Advanced Land Observing Satellite, have been used to map the surface displacements using the Persistent Scatterer Interferometry technique. The use of Phased Array Type L-band Synthetic Aperture Radar data has proved useful for avoiding signal decorrelation and estimating surface deformation in the heavily vegetated study region. The technique enables the monitoring of continuous small displacements over a large area. Our findings present that many Persistent Scatterers were located on the vegetation cover. The results reveal areas of ground surface subsidence up to 44 mm/year that are well correlated with the underground coal mining galleries particularly in the Gelik region where the Karadon mining galleries are present.
Keywords: InSAR; Persistent scatterer; Coal mining; Land subsidence; Time series analysis; PERMANENT SCATTERERS; DEFORMATION; RADAR; BASIN; Environmental Sciences & Ecology; Geology; Water Resources